Blood Flow in the Scaphoid Is Improved by Focused Extracorporeal Shock Wave Therapy. Issue 1 (January 2020) - Schleusser, Sophie; Song, Jungin; Stang, Felix Hagen; Mailaender, Peter; Kraemer, Robert; Kisch, Tobias
Abstract: Background: Extracorporeal shock wave therapy (ESWT) has shown benefits in patients with nonunion or delayed bone healing, pseudarthrosis, and avascular necrosis of bone. Until now, these effects were explained by the release of growth factors, activation of cells, and microfractures occurring after ESWT. Microcirculation is an important factor in bone healing and may be compromised in fractured scaphoids because its blood supply comes from the distal end. Due to this perfusion pattern, the scaphoid bone is prone to nonunion after fracture. The ability of ESWT to enhance microcirculation parameters in soft tissue was of interest to determine if it improves microcirculation in the scaphoid. Questions/purposes: (1) Does capillary blood flow increase after a single session of ESWT in the scaphoid? (2) Do oxygen saturation in the bone and postcapillary venous filling pressure increase after a single session of ESWT in the scaphoid? Methods: ESWT (0.3 mJ/mm 2, 8Hz, 1000 impulses) was applied to the intact scaphoid of 20 volunteers who were without wrist pain and without any important metabolic disorders. Mean age was 43 ± 14 years, 12 men and eight women (40% of total). Volunteers were recruited from January 2017 to May 2017. No anesthetic was given before application of ESWT. An innovative probe designed for measurements in bone by compressing soft tissue and combining laser-Doppler flowmetry and spectrophotometry was used to noninvasively measure parameters of microcirculation in the scaphoid. Blood flow, oxygenation, and venous filling pressure were assessed before and at 1, 2, 3, 5, 10, 15, 20, 25, and 30 minutes after ESWT application. Room temperature, humidity, ambient light and measuring sequences were kept consistent. A paired t-test was performed to compare experimental data with baseline (p < 0.05 taken as significant). Results: At baseline, capillary blood flow of the bone was 108 ± 46 arbitrary units (AUs) (86 to 130). After treatment with ESWT, it was 129 ± 44 AUs (106 to 150; p = 0.011, percentage change of 19 %) at 1 minute, 138 ± 46 AUs (116 to 160; p = 0.002, percentage change of 28%) at 2 minutes, 146 ± 54 AUs (121 to 171; p = 0.002, percentage change of 35%) at 3 minutes and 150 ± 52 AUs (126 to 174; p < 0.001, percentage change of 39%) at 5 minutes. It remained elevated until the end of the measuring period at 30 minutes after treatment at 141 ± 42 AUs (121 to 161; p = 0.002) versus baseline). Oxygen saturation and postcapillary venous filling pressure in bone showed no change, with the numbers available. Conclusions: A single session of ESWT increased capillary blood flow in the scaphoid during measuring time of 30 minutes. Bone oxygenation and postcapillary venous filling pressure, however, did not change. Because increased oxygenation is needed for improved bone healing, it remains unclear if a sole increase in capillary blood flow can have clinical benefits. As the measuring period was limited to only 30 minutes, bone oxygenation and postcapillary filling pressure may subsequently show change only after the measuring-period ended. Clinical Relevance: Further studies need to evaluate if increased capillary blood flow can be sustained for longer periods and if bone oxygenation and postcapillary venous filling pressure remain unchanged even after prolonged or repetitive ESWT applications. Moreover, clinical studies must validate if increased microcirculation has a positive impact on bone healing and to determine if ESWT can be therapeutically useful on scaphoid fractures and nonunions.